1996
DOI: 10.1074/jbc.271.23.13649
|View full text |Cite
|
Sign up to set email alerts
|

p130Cas, a Substrate Associated with v-Src and v-Crk, Localizes to Focal Adhesions and Binds to Focal Adhesion Kinase

Abstract: p130(Cas) (crk associated substrate) has the structural characteristics of an adapter protein, containing multiple consensus SH2 binding sites, an SH3 domain, and a proline-rich domain. The structure of p130(Cas) suggests that it may act to provide a framework for protein-protein interactions; however, as yet, its functional role in cells is unknown. In this report we show that p130(Cas) is localized to focal adhesions. We demonstrate that p130(Cas) associates both in vitro and in vivo with pp125(FAK) (focal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
311
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(325 citation statements)
references
References 43 publications
11
311
3
Order By: Relevance
“…Cas forms a stable complex with v-Crk and c-Crk in a phosphorylation-dependent manner and is a substrate for Src-family kinases (Vuori et al, 1996). That Cas was phosphorylated on tyrosine in the absence of insulin can be explained by adhesion-induced tyrosine phosphorylation of Cas (Nojima et al, 1995;Vuori and Ruoslahti, 1995 was found to be tyrosine-phosphorylated in some continuously adherent cells (Harte et al, 1996;Ribon and Saltiel, 1996). We observed a decreased association of Crk with Cas after insulin treatment.…”
Section: Interaction Between Crk and Irs-1mentioning
confidence: 99%
“…Cas forms a stable complex with v-Crk and c-Crk in a phosphorylation-dependent manner and is a substrate for Src-family kinases (Vuori et al, 1996). That Cas was phosphorylated on tyrosine in the absence of insulin can be explained by adhesion-induced tyrosine phosphorylation of Cas (Nojima et al, 1995;Vuori and Ruoslahti, 1995 was found to be tyrosine-phosphorylated in some continuously adherent cells (Harte et al, 1996;Ribon and Saltiel, 1996). We observed a decreased association of Crk with Cas after insulin treatment.…”
Section: Interaction Between Crk and Irs-1mentioning
confidence: 99%
“…myrFAK was immunprecipitated with anti-V5 and immunoblotted for the coexpressed p130Cas. Deletion of PR-1, reported as the primary binding site for p130Cas (Harte et al, 1996;Polte and Hanks, 1995), resulted in a noticeable decrease in the amount of p130Cas⌬SD binding ( Fig. 5d, lane 4).…”
Section: Myristoylated Fak Suppresses Anoikis In Mecs and Mefsmentioning
confidence: 99%
“…FAK contains two proline rich (PR) domains, which can interact with the SH3-domain-containing proteins (Harte et al, 1996;Hildebrand et al, 1996;Polte and Hanks, 1995). We generated myrFAK constructs lacking either or both PR domains (Fig.…”
Section: Myristoylated Fak Suppresses Anoikis In Mecs and Mefsmentioning
confidence: 99%
“…The SH3 domain of p130 Cas is required to rescue inhibition of cell spreading by p130 Cas siRNA p130 Cas interacts with FAK primarily via binding of its SH3 domain to the FAK proline-rich region, spanning amino acids 712 to 718 (Polte and Hanks, 1995;Harte et al, 1996), and this region is necessary for association of p130 Cas with focal adhesions in Cos-7 cells and Srctransformed NIH3T3 cells (Nakamoto et al, 1997). We sought to confirm a role for FAK signaling through p130 Cas in regulation of cell spreading by knocking out endogenous expression of p130 Cas and re-expressing either wild type or SH3 domain-deleted rat p130 Cas .…”
Section: Fak and Pyk2 Sirna Transfection Stimulates Cell Spreading Inmentioning
confidence: 99%